An Unknown Seal of the Convent of Cluj-Mănăștur - ȘTEFAN, Andrei-Alexandru (Studia Universitatis Babeș-Bolyai Historia, 2017)
The present paper wishes to examine the possibility regarding the existence of an unknown seal of the convent of Cluj-Mănăştur, one of the two major places of authentication in Late Medieval Transylvania. Starting from original documents dating back to the first decades of the 14th century, preserved by the national archives systems of Hungary and Romania, after detailed analyses one could observe the presence of several sealing traces of an ogival form, in contrast to the two round seals known by the subject’s historiography and used successively up to the mid-16th century. Therefore, the purpose of the present work is to bring several clarifications regarding these seal fragments, which in the end reveal themselves as one of the fundamental characteristic from the beginnings of this place of authentication. Rezumat: Un sigiliu necunoscut al conventului de la Cluj-Mănăștur. Lucrarea de faţă îşi propune să examineze posibilitatea existenței unui sigiliu rămas până în prezent necunoscut al conventului benedictin de la Cluj-Mănăştur, unul dintre cele două locuri de adeverire majore ale Transilvaniei Evului Mediu Târziu. Pornind de la documente originale datând din primele decenii ale secolului al XIV-lea, păstrate în sistemele arhivelor naționale din Ungaria și România, în urma unor analize detaliate, s-au putut observa conservarea unor fragmente sigilare de formă ogivală, spre deosebire de cele două sigilii rotunde cunoscute istoriografiei subiectului ca fiind utilizate succesiv până la mijlocul secolului al XVI-lea. Prin urmare, scopul prezentului demers este de a aduce o serie de lămuriri cu referire la aceste resturi sigilare, care se dezvăluie drept una dintre caracteristicile fundamentale ale începuturilor acestui loc de adeverire. Cuvinte-cheie: practică sigilară, sigiliu ogival, loca credibilia, diplomatică, abate.